2020
DOI: 10.1002/lary.29237
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke and Myocardial Infarction After Sudden Sensorineural Hearing Loss: A Meta‐Analysis

Abstract: Objectives/Hypothesis: The pathophysiology of idiopathic sudden sensorineural hearing loss (ISSNHL) is still unknown, but labyrinthine artery infarction has been proposed. The objective of this study was to perform a systematic review and conduct a meta-analysis assessing the risk of developing stroke and myocardial infarction after presentation with ISSNHL.Methods: A systematic literature review was conducted using Pubmed, Embase, Web of Science, and Cochrane Libraries. All studies investigating an associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 47 publications
(184 reference statements)
0
28
0
Order By: Relevance
“…In the present study, the cases were identified as idiopathic taking into account our exhaustive protocol, which excludes classic viral/infectious, vascular, autoimmune, and oncological causes. Accordingly, other studies 2 5 6 7 13 15 were published, which attempted to correlate ISSHL with other potential risk factors such as cardiovascular, metabolic, or autoimmune conditions. One of the factors that will definitely help to explain the pathophysiological mechanism, and even refine the diagnosis of sudden hearing loss, is the improvement in imaging exams, namely high-field magnetic resonance imaging of the inner ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cases were identified as idiopathic taking into account our exhaustive protocol, which excludes classic viral/infectious, vascular, autoimmune, and oncological causes. Accordingly, other studies 2 5 6 7 13 15 were published, which attempted to correlate ISSHL with other potential risk factors such as cardiovascular, metabolic, or autoimmune conditions. One of the factors that will definitely help to explain the pathophysiological mechanism, and even refine the diagnosis of sudden hearing loss, is the improvement in imaging exams, namely high-field magnetic resonance imaging of the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 5 On the other hand, ISSHL was regarded as a possible sign preceding the development of ischemic stroke. 5 6 7 Despite this evidence, it is still controversial if the occurrence of ISSHL and its recovery should be considered cardiovascular risk biomarkers. The knowledge of this association would be important for the treatment of ISSHL and to address these cardiovascular preconditions in ISSHL patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing studies have confirmed that ALB plays an important role in the occurrence and development of cardiovascular and cerebrovascular diseases (13)(14)(15). Several studies indicated that SSNHL has similar pathogenesis with cardiovascular and cerebrovascular diseases (16)(17)(18). The determination of ALB values could be of prognostic value in acute inflammation and hemodynamic disorders related to SSNHL.…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9][10][11] However, past reviews reported evidence until 2014 and did not report information from some CVRFs (high levels of triglycerides [TG], high-density lipoprotein cholesterol [HDL-c], and metabolic syndrome [MetS]) 7 issues that are addressed in the present work. It was also suggested that patients with ISSNHL had a higher risk of developing future stroke, 12,13 although ISSNHL was not associated with future acute myocardial infarction. 13,14 Quaranta et al reported signs of endothelial dysfunction in ISSNHL and Fisch described the blood pressure dysregulation of the stria vascularis (a process related to age and CVRFs) as a consequence of cochlear atherosclerosis, in which the tunica adventitia loses fibroblasts and becomes thicker, which in turn leads to plasmatic viscosity and platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that patients with ISSNHL had a higher risk of developing future stroke, 12,13 although ISSNHL was not associated with future acute myocardial infarction. 13,14 Quaranta et al reported signs of endothelial dysfunction in ISSNHL and Fisch described the blood pressure dysregulation of the stria vascularis (a process related to age and CVRFs) as a consequence of cochlear atherosclerosis, in which the tunica adventitia loses fibroblasts and becomes thicker, which in turn leads to plasmatic viscosity and platelet aggregation. [15][16][17] As a consequence, vascular pathology is supposed an important etiological factor of ISSNHL.…”
Section: Introductionmentioning
confidence: 99%